2014
DOI: 10.4236/jct.2014.54040
|View full text |Cite
|
Sign up to set email alerts
|

ALDH Activity Correlates with Metastatic Potential in Primary Sarcomas of Bone

Abstract: Osteosarcoma (OS), chondrosarcoma (CSA), and Ewings sarcoma (ES) are the most common primary malignancies of bone, and are rare diseases. As with all sarcomas, the prognosis of these diseases ultimately depends on the presence of metastatic disease. Survival is therefore closely linked with the biology and metastatic potential of a particular bone tumor’s cells. Here we describe a significant correlation of aldehyde dehydrogenase (ALDH) activity and the presence/absence of distant metastases in ten consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 26 publications
3
43
0
3
Order By: Relevance
“…A subpopulation of ALDH1 high MG63 cells was detected by Honoki et al (25) who further reported ALDH1 high cells to have increased expression of stem-like genes (Nanog, Oct3/4, Stat3, Sox2), higher resistance to doxorubicin and cisplatin and increased self-renewal ability as shown by sphere formation. Importantly, ALDH high cells were also detected in human osteosarcoma samples and increased ALDH activity was further correlated to metastatic potential (26). It was also shown that inhibition of ALDH activity using disulfiram resulted in reduced cell proliferation suggesting direct targeting of CSC phenotype cells.…”
Section: Aldehyde Dehydrogenase (Aldh)mentioning
confidence: 78%
“…A subpopulation of ALDH1 high MG63 cells was detected by Honoki et al (25) who further reported ALDH1 high cells to have increased expression of stem-like genes (Nanog, Oct3/4, Stat3, Sox2), higher resistance to doxorubicin and cisplatin and increased self-renewal ability as shown by sphere formation. Importantly, ALDH high cells were also detected in human osteosarcoma samples and increased ALDH activity was further correlated to metastatic potential (26). It was also shown that inhibition of ALDH activity using disulfiram resulted in reduced cell proliferation suggesting direct targeting of CSC phenotype cells.…”
Section: Aldehyde Dehydrogenase (Aldh)mentioning
confidence: 78%
“…ALDH expression also appears to be linked with metastatic potential. Semisolid matrigel matrix invasion assays showed a correlation between ALDH levels and increased invasiveness when comparing two murine OS cell lines [7]. OS cells treated with disuliram, an ALDH-inhibitor, show reduced ALDH expression and altered cellular morphology, with fewer invadopodia and greater shape uniformity [6,15,16].…”
Section: Aldehyde Dehydrogenase (Aldh)mentioning
confidence: 98%
“…Aldehyde dehydrogenases (ALDHs) are a superfamily of nicotinamide adenine dinucleotide phosphate (NADP + )-dependent tetrameric enzymes that participate in aldehyde metabolism via catalysis of exogenous and endogenous aldehydes into their corresponding carboxylic acids and the cell's resistance to oxidative stress [4][5][6][7]. Inhibition of ALDH can lead to a buildup of aldehydes that can lead to toxic side-efects, which include enzyme inactivation, DNA damage, impairment of cellular homeostasis, and cell death by forming adducts with various cellular targets [4,8,9].…”
Section: Aldehyde Dehydrogenase (Aldh)mentioning
confidence: 99%
See 1 more Smart Citation
“…Эпителиальный мембранный антиген регулярно экспрессируется в хордоме [43]. [44,45]. О разнообразных формах проявле-ния «эпителиальных» качеств остеосаркомы свидетель-ствуют многочисленные публикации -описаны как эпи-телиоидные варианты опухоли с образованием плоскокле-точных жемчужин с гландулярным компонентом, так и морфологически типичные остеосаркомы с эпителиаль-ным иммунофенотипом [4,43,46].…”
Section: Introductionunclassified